La acreditación mexicana desde una perspectiva comparativa - De Vries, Wietse (Revista Complutense de Educación, 2007)
Mexico formally set up a system of program and institutional accreditation in 2000. The workings of this system are, at first sight, very similar to processes in place in the European Union and other countries, but several contextual factors produce results that are markedly different from those in other places. From a comparative perspective, this article points out that the implementation of an accreditation system not only depends on technical decisions, but that several political, legal and cultural conditions can seriously hamper the system in practice.